PENERAPAN SAK EMKM DALAM PENYUSUNAN LAPORAN KEUANGAN UMKM PADA CV. MALABO ARSITEK MAKASSAR - Saputra, Iswan Jaya; Rijal, Abdul; S, Masnawaty (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2024)
This research aims to analyze the implementation of SAK EMKM in the preparation of financial statements for UMKM at CV. Malabo Arsitek Makassar. The data collection method used is triangulation, which is a combination of interviews, observations, and documentation. The types and sources of data used are primary and secondary, while the analysis method follows the approach proposed by Miles and Huberman. Based on the research findings, it can be concluded that the application of SAK EMKM in the preparation of financial statements by CV. Malabo Arsitek does not adhere to the appropriate SAK EMKM standards. This is attributed to the inadequacy of human resources responsible for managing the financial reports of CV. Malabo Arsitek. Additionally, the incorrect format of the financial statements has led to incomplete financial reporting. Therefore, the author recommends that CV. Malabo Arsitek improve the quality of its human resources, especially those involved in financial report management, by studying and understanding SAK EMKM. Furthermore, they should promptly adopt a financial statement format that complies with the applicable standards.